Supernova and The Struggle for Gender Equality - Mytha Candria (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
In this article, I present a semiotic study of Dee’s novel Supernova, but the analysis is focused on the female character Diva or Supernova, which plays as the symbol of Dee’s struggle for gender equality. Following Chandler (2007), I made use of the Saussurean and Peircean semiotics, in which signs consist of inseparable signifiers and signifieds, and the modes of their relationships are icon, index, and symbol. In the succeeding discussion, I argue that the title of the novel functions as an index that directs the readers’ attention to the character Diva (Supernova). Supernova is a metaphor (iconic and symbolic) of an individual who is able to enlighten the life of others with wisdom. She also functions as a symbol of strong oppositions to patriarchy, in which good women are simplistically defined with reference to their marriage and family life. There are hundreds of reasons defining a good woman, including maturity, self-awareness, knowledge and compassion. Another metaphorical use of Supernova relates to the fact that she, because of all her qualities, serves as an Avatar, something uncommon in Indonesian context. Appointing a woman and a prostitute as an Avatar means a challenge to Indonesia’s religious patriarchy.Keywords: Supernova; semiotics; icon, index, symbol; gender equality